Rola byłych funkcjonariuszy komunistycznych służb specjalnych w cywilnym wywiadzie i kontrwywiadzie Polski i Czech w latach 1989– 2018 - Graca, Witold; Spustek, Henryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Czech civilian special services after 1989 were built by former officers of the communist services. In Poland and in the Czech Republic, at least at the beginning of the changes, participation in the services of members of the democratic opposition was symbolic. The officers of the communist services in both countries were gradually removed during subsequent reorganizations in the years 1990–2018. In the Czech Republic they have not been completely removed to this day. The Czech authorities deprived them of financial powers acquired in the service of a totalitarian system. The Polish authorities also deprived former security officers of the privileges acquired in service before systemic changes and additionally those already acquired at work for a democratic state. However, the financial severity of both solutions is incomparable due to differences in pension systems of uniformed services between both countries.
Keywords: emerytura; polska służba bezpieczeństwa; czeska służba bezpieczeństwa